Exchange bias e magnetização reversa : um estudo em compostos do tipo TRCrO3 (TR = Nd, Dy, Pr) - Jesus, Jônathas Rafael de (2019)
In this work, the structural and magnetic properties of TRCrO3 (TR = Dy, Nd and Pr) orthochromites obtained by the chemical co-precipitation method were studied. The structural characterization was performed by X-ray diffraction (XRD) and analyzed by Rietveld refinement. Magnetization measurements as a function of field (MvsH) and temperature (MvsT) and X-ray magnetic circular dichroism (XMCD) were performed to understand the magnetic properties of the compounds. The XRD analyzes show that both studied systems present orthorhombic symmetry: space group is Pbnm for the NdxPr1-xCrO3 (0 ≤ x ≤ 1) system and Pnma for the DyxNd1-xCrO3 (0,01 ≤ x ≤ 1) samples. Both systems presented changes in the cell parameters as a function of the amount of Nd3+, and the magnetic order is a predominantly antiferromagnetic. In the particular of case, the Nd0.5Pr0.5CrO3 sample, it shows a negative magnetization, which increasing with the increasing of the magnetic field during the Field-Cooled Cooling (FCC) measurement. The inverse magnetic susceptibility curves as a function of temperature were fitted for of the DyxNd1-xCrO3 system. It demonstrates that strength of antisymmetric interaction increases with increasing of Dy3+. MvsH measurements performed at T = 100 K for the DyxNd1-xCrO3 system showed the existence of a weak ferromagnetic component indicated by the presence of hysteresis at low field regions. These results also show the presence of two maximum in the coercive field as a function of temperature for samples with x < 0.3, whose widths of peaks are not similar to previous works. Moreover, these measurements also present the presence of Exchange Bias (EB), which should be directly related to strength of symmetric and antisymmetric interaction magnetic. A detailed investigation in the Dy0.2Nd0.8CrO3 sample also show the presence of positive EB below T = 5 K confirmed in MvsH curves performed in T = 3 K using several cooling fields. This temperature coincides with the crossing of the ZFC-FC curves that should be associated to the Nd3+ ordering. In addition, XMCD measurements were performed at the Cr L2,3 edges at T = 30 K with magnetic field of 4 T suggests the presence of AFM canted.